Penguatan Unit Bisnis Pondok Pesantren Al Asror Kecamatan Gunungpati Kota Semarang - Fachrurrozie Fachrurrozie; Widiyanto Widiyanto; Ahmad Nurkhin; Satsya Yoga Baswara; Muhammad Feriady (STIKes Ibnu Sina Ajibarang, 2023)
Al Asror Islamic boarding school has several business units which are expected to be a means of developing student entrepreneurship in addition to supporting the boarding school independently. The santri craft business unit, grocery store unit, laundry and canteen are managed by the santri in the Islamic boarding school environment. The problems faced in developing student entrepreneurship are from the perspective of students as the main object of entrepreneurship education.The solution to problems in this service activity is by carrying out FGD activities, coaching and mentoring, and business motivational lectures. The target participants are students, caregivers, administrators, parents/guardians of students, and business and entrepreneurship practitioners/experts. The FGD resource persons were the service team and cottage caretakers. The targets of motivational training are students who have been involved in managing the Islamic boarding school business unit. Motivational lecture speakers are members of the service team. The stages of implementing service activities are the pre-implementation stages of service activities, the stages of implementing service activities, and the post-service activity stages. Service activities can run well and smoothly and consist of three sub-activities, namely delivering entrepreneurship material in the general stage, FGD for stakeholders, and mentoring for students who run Islamic boarding school business units. The first and second activities were carried out successfully. Islamic boarding school stakeholders can convey ideas and concepts in developing student entrepreneurship and Islamic boarding school business units. The third activity has also been carried out by providing reinforcement for students who receive the mandate to run Islamic boarding school business units such as laundry, drinking water, canteen, and others. New business ideas for Islamic boarding schools must be analyzed carefully considering the potential and development of the Patemon area and its surroundings.